Outcomes of cognitive behaviour therapy for obsessive–compulsive disorder in young people with and without autism spectrum disorders: A case controlled study. Issue 1 (30th July 2015) - Murray, Kim; Jassi, Amita; Mataix-Cols, David; Barrow, Faye; Krebs, Georgina
Abstract: Obsessive–compulsive disorder (OCD) and autism spectrum disorders (ASD) are highly co-morbid. It is suggested that youth with ASD will respond less well to cognitive behaviour therapy (CBT), as compared to their typically developing counterparts. To date there is no empirical evidence to support this view. The current study sought to compare CBT for OCD outcomes among youth with and without ASD. 22 young people with ICD-10 diagnoses of OCD and ASD (OCD+ASD) were matched with 22 youth with OCD, but no ASD (OCD+NoASD) according to base line OCD symptom severity, age, and gender. Outcomes were assessed for the two groups following a course of individually tailored, but protocol-driven CBT for OCD. While both groups responded to treatment the OCD+ASD group׳s outcomes were inferior to the OCD+NoASD group, as indicated by a significantly smaller decrease in symptoms over treatment (38.31% vs. 48.20%) and lower remission rates at post-treatment (9% vs. 46%). Overall, young people experiencing OCD in the context of ASD benefitted from CBT, but to a lesser extent than typically developing children. Recent efforts to modifying standard CBT protocols for OCD in ASD should continue in order to optimise outcomes among youth with this particular dual psychopathology. Highlights: Comparing CBT outcomes of youth with OCD and ASD with a matched OCD sample. Remission rates were reduced in youth with OCD and ASD. This is the first paper to show youth with ASD and OCD benefit less from standard CBT. Our findings highlight the need for modified CBT for individuals with ASD and OCD.